How great products and services supply great user experiences - Brunner, Robert 1958- (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from Do you matter?: how great design will make people love your company (ISBN: 9780137142446) by Robert Brunner and Stewart Emery. How to make sure customer experience permeates every corner of your company--and all your products and services"--Resource description page.
Includes bibliographical references
Keywords: Industrial design; Industrial design coordination; Branding (Marketing); Customer relations; Customer services; Design; Design; Coordination; Stratégie de marque; Service à la clientèle; industrial design; design (discipline); branding; ART / Folk & Outsider Art; CRAFTS & HOBBIES / Folkcrafts